2017
DOI: 10.1016/j.jjcc.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-mediated drug delivery system for atherosclerotic cardiovascular disease

Abstract: Administration of drugs and other therapeutic agents has been the central strategy of contemporary medicine for cardiovascular disease. The use of drug delivery systems (DDS) includes micelles, liposomes, polymeric nanoparticles, dendrimers, carbon nanotubes, and crystalline metals. Nano-DDS modify in vivo drug kinetics, depending on (patho)physiological mechanisms such as retard excretion, vascular permeability, and incorporation by mononuclear phagocyte systems, which constitute the 'passive-targeting' prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 36 publications
0
70
0
1
Order By: Relevance
“…These studies have confirmed that P-NP at a 100 to 840-fold lower single dose appears to be as effective as a cumulative systemic dose of pitavastatin (6,7). The properties of NP-DDS may be the result of two major mechanisms: i) Recognition and incorporation by the mononuclear phagocyte system (monocytes, macrophages and neutrophils), which may affect the blood circulation time and tissue/cell distribution of drugs delivered by the NP-DDS; and ii) enhanced vascular permeability contributing to enhanced drug delivery for atherosclerotic arterial walls and macrophages (28). In the present study, FITC-NP was still detected in the atherosclerotic plaque 7 days after a single administration, leading to the conclusion that FITC-NP may be recognized and incorporated by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have confirmed that P-NP at a 100 to 840-fold lower single dose appears to be as effective as a cumulative systemic dose of pitavastatin (6,7). The properties of NP-DDS may be the result of two major mechanisms: i) Recognition and incorporation by the mononuclear phagocyte system (monocytes, macrophages and neutrophils), which may affect the blood circulation time and tissue/cell distribution of drugs delivered by the NP-DDS; and ii) enhanced vascular permeability contributing to enhanced drug delivery for atherosclerotic arterial walls and macrophages (28). In the present study, FITC-NP was still detected in the atherosclerotic plaque 7 days after a single administration, leading to the conclusion that FITC-NP may be recognized and incorporated by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…NPs are attractive nanocarriers with therapeutic applications in the early detection of biomarkers and the treatment of vascular diseases. [19][20][21][22] Surface modification, such as by the layer-bylayer (LbL) technique, can be used to control the half-life of the encapsulated drug in the system. The fabrication of LbL NPs by alternately coating oppositely charged polymers or biomolecules on various colloids can produce a promising delivery system with high loading efficiency, easy functionalization, tunable multifunctionality, and responsiveness to stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…NDDSs refer to material in which at least one dimension is in the range of nanometer scale (1-100 nm) or composed of them as basic units in three-dimensional space (Cooke and Atkins, 2016;Zhou et al, 2018). As an effective means to optimize the drug delivery, NDDSs have become a research hotspot in the field of pharmacy and modern biomedicine (Matoba et al, 2017). The investigation of NDDSs has been for more than 40 years, creating a mass of nano-drug carriers.…”
Section: Types Of the Nddssmentioning
confidence: 99%